2022
DOI: 10.3389/fmicb.2021.792530
|View full text |Cite
|
Sign up to set email alerts
|

Armillaria mellea Symbiosis Drives Metabolomic and Transcriptomic Changes in Polyporus umbellatus Sclerotia

Abstract: Sclerotia, the medicinal part of Polyporus umbellatus, play important roles in diuresis and renal protection, with steroids and polysaccharides as the main active ingredients. The sclerotia grow and develop only after symbiosis with Armillaria sp. In this study, a systematic metabolomics based on non-targeted UPLC-MS method was carried out between the infected part of the separated cavity wall of the sclerotia (QR) and the uninfected part (the control group, CK) to find and identify differential metabolites. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…At present, over 40 species of Armillaria have been described in the world, some of which are serious tree pathogens, some have medicinal value, and some can coexist with G. elata Bl. for its cultivation and production [18][19][20]. There are 15 Armillaria species in China, of which eight are endemic to China [21].…”
Section: Introductionmentioning
confidence: 99%
“…At present, over 40 species of Armillaria have been described in the world, some of which are serious tree pathogens, some have medicinal value, and some can coexist with G. elata Bl. for its cultivation and production [18][19][20]. There are 15 Armillaria species in China, of which eight are endemic to China [21].…”
Section: Introductionmentioning
confidence: 99%
“…As parasitic fungi, Armillaria can parasitize more than 500 tree species causing root rot, leading to potentially substantial economic losses [ 2 ]. Interestingly, Armillaria mellea , one of these fungi, has also been observed to establish a symbiotic relationship with the original plant of traditional Chinese medicine (TCM), such as Gastrodia elata (an orchid) and the fungus Polyporus umbellatus (sclerotia) [ 3 , 4 ]. Without Armillaria , G. elata could not grow at all [ 5 ], which would lead to over ten billion economic losses, as was the case with P. umbellatus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rhizomorphs spread throughout the soil in search of nutrients derived from both decaying wood and living tree roots [ 11 , 12 ]. Importantly, the rhizomorphs of Armillaria have similarly been characterized as functional structures during the colonization of G. elata (Orchid) protocorm and P. umbellatus sclerotia [ 3 , 4 ]. Our previous studies indicated that metabolic pathways involved in steroids, etc., were active and enriched during the infection of P. umbellatus sclerotia by A. mellea by metabolic and transcriptomic analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…elata digests the symbiotic Armillaria mellea ( A . mellea ) to provide its nutrition [ 1 3 ]. A .…”
Section: Introductionmentioning
confidence: 99%